Developing Mathematics Assessment Instrument for Children with Autism Spectrum Disorder - Oom Sitti Homdijah; Euis Heryati; Ehan Ehan (Jurusan Pendidikan Luar Biasa, Fakultas Ilmu Pendidikan, Universitas Negeri Malang, 2021)
Academic assessment instruments are necessary for obtaining data about student learning needs. Teachers need assessment instruments to collect accurate information as a reference in devising learning programs. The development of mathematics assessment instrument for children with autistic spectrum needs to be carried out to produce valid and easy-to-use instrument for teachers to assess their students' mathematical abilities. This research results showed that the developed instrument consisting of four aspects, including numbers, counting operations, place-values, and fractions. The validity check revealed that this instrument could be considered as valid and usable.